DFT-B3LYP study of interactions between host biphenyl-1-aza-18-crown-6 ether derivatives and guest Cd2+: NBO, NEDA, and QTAIM analyses - Behjatmanesh-Ardakani, R. (Springer Verlag (Germany), 2016)
This report present the results of natural energy decomposition analysis (NEDA), natural bond orbital (NBO), and quantum theory of atoms in molecules (QTAIM) calculations of three derivatives of biphenyl-1-aza-18-crown-6 ether and their 1:1 complexes with Cd2+. All calculations used the B3LYP density functional theory in combination with the 6-311G and WTBS basis sets for ligands and Cd2+ ion, respectively. Ligands 1 and 3 have a single 1-aza-18-crown-6, substituent; ligand 2 has two such substituents. The results show that, in the optimized geometries of the complexes, the distance between N and Cd2+ is greater than the distance between O and Cd2+. NBO and QTAIM data confirm these results. There was no stabilization energy or bond critical point for N · · · Cd2+ in NBO or QTAIM, respectively. Data show that the O · · · Cd2+ interaction is a kind of closed shell interaction. The trend of the calculated stabilization energy was similar to the experimental data. Different contributions of interaction energies for complex formation were analyzed by NEDA, and the results show that the main component of the interactions is accounted for by polarization.